Precautionary savings and the importance of business owners - Erik Hurst; Arthur Kennickell; Annamaria Lusardi; Francisco Torralba (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
In this paper, we show the pivotal role business owners play in estimating the importance of the precautionary saving motive. The fact that business owners hold higher-than-average wealth while facing higher income risk than other households leads to a correlation between wealth and labor income risk regardless of whether or not a precautionary motive is important. Using data from the Panel Study of Income Dynamics in the 1980s and the 1990s, we show that within separate samples of both business owners and non-business owners the size of precautionary savings with respect to labor income risk is modest and accounts for less than ten percent of total household wealth. However, pooling together these two groups leads to an artificially high estimate of the importance of precautionary savings. Data from the Survey of Consumer Finances further confirms that precautionary savings account for less than ten percent of total wealth for both business owners and non-business owners. Thus, while a precautionary saving motive exists and affects all households, it does not give rise to high amounts of wealth in the economy, particularly among those households who face the most volatile labor earnings.
urn:nbn:de:hebis:30-29443
Keywords: D91; 330; Income Risk; Household Wealth; Entrepreneurship; Sparen; Kassenhaltungsansatz; Unternehmer; USA